World report on child injury prevention - Peden, M. M; Peden, M. M. (Geneva, Switzerland World Health Organization [New York, NY] UNICEF, 2008)
"Child injuries have been neglected for many years, and are largely absent from child survival initiatives presently on the global agenda. Through this World report on child injury prevention, the World Health Organization, the United Nations Children's Fund and many partners have set out to elevate child injury to a priority for the global public health and development communities. The knowledge and experience of nearly two hundred experts from all continents and various sectors were invaluable in grounding the report in the realities faced in many countries. This World report on child injury prevention should be seen as a complement to the UN Secretary-General's study on violence against children released in late 2006. That report addressed violence-related or intentional injuries. Both reports suggest that child injury and violence prevention programmes need to be integrated into child survival and other broad strategies focused on improving the lives of children. Evidence demonstrates the dramatic successes in child injury prevention in countries which have made a concerted effort. These results make a case for increasing investments in human resources and institutional capacities. This would permit the development, implementation and evaluation of programmes to stem the tide of child injury and enhance the health and well-being of children and their families the world over. Implementing proven interventions could save more than a thousand children's lives a day." - p. vii
Child injuries in context -- Road traffic injuries -- Drowning -- Burns -- Falls -- Poisonings -- Conclusions and recommendations.
Keywords: Children; Accident Prevention; Wounds and Injuries; Child; Child Welfare